1992
DOI: 10.1523/jneurosci.12-08-03084.1992
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic pharmacology of the superior olivary complex studied in mouse brain slice

Abstract: The synaptic pharmacology of the lateral superior olive (LSO) and medial nucleus of the trapezoid body (MNTB) was examined in a brain slice preparation of the mouse superior olivary complex (SOC) , 1967;Moore et al., 1974;Casseday and Neff, 1975;Jenkins and Masterton, 1982;Kavanagh and Kelly, 1986). Neurons in the SOC receive binaural input and are sensitive to small interaural time and intensity differences that serve as cues for sound source position (Masterton and Imig, 1984;Phillips and Brugge, 1985). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 87 publications
4
52
3
Order By: Relevance
“…These PSPs had onset latencies of 5.5±0.8 ms (n = 6) in P1-P2 mice and 5.0±0.5 ms (n = 13) in P4-P7 mice. These values are comparable to those reported for newborn rats [11] and gerbils [15] and about 3 ms longer than the latencies reported for 3-week-old mice [17]. In slices prepared from P1 and P2 mice MNTB-evoked PSPs (recorded in perforatedpatch mode) were always depolarizing from the resting membrane potential (n = 8, V rest −51.8 ± 1.4 mV) (Fig.…”
supporting
confidence: 88%
“…These PSPs had onset latencies of 5.5±0.8 ms (n = 6) in P1-P2 mice and 5.0±0.5 ms (n = 13) in P4-P7 mice. These values are comparable to those reported for newborn rats [11] and gerbils [15] and about 3 ms longer than the latencies reported for 3-week-old mice [17]. In slices prepared from P1 and P2 mice MNTB-evoked PSPs (recorded in perforatedpatch mode) were always depolarizing from the resting membrane potential (n = 8, V rest −51.8 ± 1.4 mV) (Fig.…”
supporting
confidence: 88%
“…In the present study, similar signals were observed when using electrodes with impedances of approximately 6 MW. An increase in electrode impedance resulted in the signal waveforms becoming more biphasic, similar to the waveforms shown by Wu and Kelly (1992).…”
Section: Complex Waveforms In Mntb Unit Dischargesmentioning
confidence: 54%
“…The waveforms of the extracellularly recorded pre&action potential compounds described in these previous studies differed somewhat from each other, but these differences most probably only reflect different recording conditions (Pfeiffer 1966;Guinan and Li 1990;Wu and Kelly 1992). The form and the polarity of extracellularly recorded signals depend on the input impedance of the recording electrode and also on the spatial relation between the tip of the electrode and the recorded neuron.…”
Section: Complex Waveforms In Mntb Unit Dischargesmentioning
confidence: 83%
See 1 more Smart Citation
“…The neurotransmitter released by the calyx of Held onto the principal neuron is glutamate (Banks and Smith 1992;Wu and Kelly 1992). Released glutamate activates AMPA and, depending on the age of the animal (Futai et al 2001; Values are means Ϯ SD.…”
Section: All Inputs Mediated By Ampa Receptorsmentioning
confidence: 99%